The emergence of fuel cell technology and challenges to latecomer countries: insights from Singapore and Malaysia - Mohamad, Z.F. (2009)
This article uses the systems of innovation approach (in this case using the technological system framework and analysis of system functions) to provide insights for understanding the challenges at latecomer countries have to face in the development of an emerging technology like fuel cells. It shows that the development of system functions in fuel cells in Singapore is higher than Malaysia, and this is shaped by four key factors: (1) Diversity of actors and the alignment of their activities; (2) synergy between energy, environment and industrial policies; (3) openness to Internationalisation; and (4) responsiveness to demonstration activities. In Singapore the stronger presence of such factors in its policy environment has had a positive influence on the development of fuel cell technology - while the absence or weaknesses of these factors might this : Contributed to the weaker and more unbalanced development in Malaysia. It is argued that this is because such factors were effective in addressing specific characteristics of the 'emerging phase' of fuel cell technology.